2003
DOI: 10.1089/153056203763317648
|View full text |Cite
|
Sign up to set email alerts
|

Treating Childhood Depression over Videoconferencing

Abstract: Effective cognitive-behavioral treatments for childhood depression have developed over the last decade, but many families face barriers to such care. Telemedicine increases access to psychological interventions by linking the child and the clinician using videoconferencing (VC). The current study evaluated an 8-week, cognitive-behavioral therapy (CBT) intervention for childhood depression either face-to-face (F2F) or over VC. The telemedicine setup included two PC-based PictureTel systems at 128 kilibits per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(206 citation statements)
references
References 39 publications
3
198
0
5
Order By: Relevance
“…Three systematic reviews rated the quality of the studies but did not use this information to make recommendations and none of them assessed the likelihood of publication bias. Common limitations in the systematic reviews were: grading of the evidence was not evident in the recommendations; studies were assessed for quality but were not linked to recommendations; all of the systematic reviews reported on the same 10 RCTs; 6,58-66 two child and adolescent RCTs [67][68] and two of the systematic reviews 23,39 included information from a further 8 moderate quality control studies. [69][70][71][72][73][74][75][76] The systematic reviews also only included studies up until 2008.…”
Section: Resultsmentioning
confidence: 99%
“…Three systematic reviews rated the quality of the studies but did not use this information to make recommendations and none of them assessed the likelihood of publication bias. Common limitations in the systematic reviews were: grading of the evidence was not evident in the recommendations; studies were assessed for quality but were not linked to recommendations; all of the systematic reviews reported on the same 10 RCTs; 6,58-66 two child and adolescent RCTs [67][68] and two of the systematic reviews 23,39 included information from a further 8 moderate quality control studies. [69][70][71][72][73][74][75][76] The systematic reviews also only included studies up until 2008.…”
Section: Resultsmentioning
confidence: 99%
“…These findings underscore the importance of developing and disseminating innovative modalities for delivering evidence-based psychotherapies to remote locations. While evidencebased psychotherapies have been shown to be effective when delivered via telephone, 23 interactive video, 24,25 and computer/Internet, 26 third-party payers frequently do not reimburse for these treatment modalities. Reimbursement for interactive video visits often requires payments to both the off-site psychotherapist and the on-site host organization (eg, primary care clinic).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 13 RCTs that evaluated treatment outcomes for mental health interventions delivered via telepsychiatry (Table 1). Seven studies targeted depression [77][78][79][80][81][82][83] , two targeted symptoms of PTSD [11,84,85] , two targeted ADHD [86] , one targeted bulimia nervosa [87] , and two targeted common psychiatric disorders presented in an outpatient medical and mental health settings.…”
Section: Treatment Outcomesmentioning
confidence: 99%